2019
DOI: 10.1108/hff-12-2018-0731
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional modelling of natural convection and entropy generation in a vertical cylinder under heterogeneous heat flux using nanofluids

Abstract: Purpose This study aims to investigate a three-dimensional computational modelling of free convection of Al2O3 water-based nanofluid in a cylindrical cavity under heterogeneous heat fluxes that can be used as a thermal storage tank. Design/methodology/approach Effects of different heat flux boundary conditions on heat transfer and entropy generation were examined and the optimal configuration was identified. The simulation results for nanoparticle (NP) volume fractions up to 4 per cent, and Rayleigh numbers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The correlations (Eqs. [5][6][7][8][9][10][11][12] are derived in the present work, using curve fitting technique by the method of least squares. The R 2 value is 99.8% and a maximum error is 1%.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlations (Eqs. [5][6][7][8][9][10][11][12] are derived in the present work, using curve fitting technique by the method of least squares. The R 2 value is 99.8% and a maximum error is 1%.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Several studies reported the effect of adding nanoparticles, without liquid-solid phase change in the core, on the enhancement of convective heat transfer flows. Examples can be found in [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . Other work studies on nanofluids can be also found in [23][24][25][26][27][28][29][30] .…”
mentioning
confidence: 99%
“…Natural convection heat transfer and total entropy generation of nanofluid in a square cavity in presence of a refrigerant rigid body was considered by Rahimi et al 17 . Recently, Rashidi et al 18 investigated a three-dimensional free convection and entropy generation of water-based nanofluid in a cylindrical cavity. Natural convection and entropy generation in an air-filled cubical cavity with active lateral walls was studied by Alnaqi et al 19 .…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the MHD effect opposes the nanofluid effect and reduces the heat transfer. Rashidi et al (2020) studied the effect of nanofluid concentration on the irreversibility production in a cylindrical cavity subjected to various boundary conditions. It was found that the addition of nanoparticles can be used as an entropy generation optimizing parameter.…”
Section: Introductionmentioning
confidence: 99%